1-3(1-4n)=12n-26

Simple and best practice solution for 1-3(1-4n)=12n-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-3(1-4n)=12n-26 equation:


Simplifying
1 + -3(1 + -4n) = 12n + -26
1 + (1 * -3 + -4n * -3) = 12n + -26
1 + (-3 + 12n) = 12n + -26

Combine like terms: 1 + -3 = -2
-2 + 12n = 12n + -26

Reorder the terms:
-2 + 12n = -26 + 12n

Add '-12n' to each side of the equation.
-2 + 12n + -12n = -26 + 12n + -12n

Combine like terms: 12n + -12n = 0
-2 + 0 = -26 + 12n + -12n
-2 = -26 + 12n + -12n

Combine like terms: 12n + -12n = 0
-2 = -26 + 0
-2 = -26

Solving
-2 = -26

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| z^2=-8-6i | | 5c+7=17 | | 2x-0.8=2.4 | | -5x^2+10x=-15 | | X^2+41x-132=0 | | 5x+9y=-75 | | 7k-21=7(k-3) | | 2x^2+12y^2-8x-12y+11=0 | | 30-12z=18 | | -3-8p=-8(-3-3p)+5 | | 3x^7=839808 | | 4x+15+107=180 | | 4(3m+8)=3(1+4m) | | 7x^2-18x-40=2x-8 | | 3x^7= | | 4+5x=11+3x | | 2x+1x-8=16 | | 5x-8=1.5 | | 7t-4=10t/14 | | x^2+12x=6x-8 | | 7(5-6x)+7=-42x-1 | | 6b^2+4b-2=0 | | (8-7i)/(2-6i) | | 11.57-3n=4.67 | | 200.00+0.25=410.00 | | 2=13+0.5x | | x^2-x+1=-7 | | x^2-x+1=1 | | 6/g=42/36 | | x^2-x+1=-1 | | a-b/x=c | | Y+7=3(x-4) |

Equations solver categories